Legal Certainty of the Rights of Wives and Children After Divorce - Siregar, Yani Arfianti; Yusrial, Yusrial; Arisman, Arisman; Lidia, Notri (Jurnal Elsyakhshi, 2023)
The position of suspicious children in the perspective of Islamic law is a topic of significant interest and importance within legal and ethical discourse. In Islamic jurisprudence, the treatment and rights afforded to children, particularly those born under suspicious circumstances, hold profound implications for both societal norms and legal frameworks. Understanding the nuanced stance of Islamic law towards suspicious children necessitates a comprehensive exploration of religious texts, legal principles, and contemporary interpretations. This research aims to see what the rights of women and children are after divorce, what is the legal certainty in fulfilling the rights of women and children after divorce in the Religious Courts, and what are the obstacles to fulfilling the rights of women and children after divorce in the Religious Courts. This research method uses a qualitative method with content analysis approach. From the research that has been carried out, it was found that legal certainty in fulfilling the rights of women and children in the religious court environment is still not effective. The issue of the rights and obligations of husband and wife in the event of divorce is closely related to the legal awareness of both parties. So there is a need for good legal awareness among the public regarding the rights and obligations of marriage. Good legal awareness has a causal relationship with the effectiveness of legal certainty of the rights of children and wives after divorce.